Pengaruh Terapi Musik Kelompok Terhadap Perilaku Kegelisahan Lansia dengan Demensia di Panti Sosial Tresna Werdha Yogyakarta Unit Budhi Luhur Kasongan, Bantul - , OLIVIA AYU SHINTA DEWI; , Sri Warsini,S.Kep.,Ns.,M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The effect of aging causes various disorders such a insomnia, stress, depressions, anxiety, dementia and delirium. The elderly with dementia may have problems of negative emotion and agitated behavior. Music therapy is one of effective therapies that can be used to minimize agitated behavior in the elderly with dementia. Objective : This study aimed to identify effect group music therapy to agitated behavior in elderly with dementia at Tresna Werdha Social Institution of Yogyakarta Budhi Luhur Unit Kasongan Bantul. Method: The study was a Quasi experiment with pre-test posttest one group design carried out at Tresna Werdha Social Institution of Yogyakarta Budhi Luhur Unit Kasongan Bnatul. Research instrument were Mini Mental State Examination (MMSE), Cohen Mansifield Agitation Inventory (CMAI). Data analysis Paired test, Wilcoxon, Chi-Square. Samples were purposively taken, comprising as many as 15 elderly. Result: Degree of agitated behavior of elderly before and after intervention of group music therapy mainly belonged to agitated category (66,7%). The result of study showed that there was no significant difference in average score of agitated behavior of the elderly before and after group music therapy (p>0,05). However, group music affected verbal behavior which was an element of agitation in elderly (p<0,05). Conclusion: There was no effects of group music therapy to agitated behavior of the elderly with dementia at at Tresna Werdha Social Institution of Yogyakarta Budhi Luhur Unit Kasongan Bantul.